A bis-naphthalimide functionalized pillar[5]arene-based supramolecular π-gel acts as a multi-stimuli-responsive material. (12th September 2018) - Zhang, You-Ming; Li, Yong-Fu; Zhong, Kai-Peng; Qu, Wen-Juan; Yao, Hong; Wei, Tai-Bao; Lin, Qi
Abstract : A novel approach for the design of multi-stimuli-responsive supramolecular functional materials was successfully developed by introducing the competition of π–π stacking and cation–π interactions into a pillar[5]arene-based supramolecular π-gel (MP5-G ). Abstract : In this work, a novel supramolecular π-gel has been constructed using a naphthalimide functionalized pillar[5]arene-based gelator (MP5 ). The gelatorMP5 simultaneously contains a naphthalimide moiety as the π⋯π interaction site as well as a fluorophore. Interestingly, theMP5 -based supramolecular π-gel (MP5-G ) exhibits strong aggregation-induced emission (AIE).MP5-G exhibited good thermal-responsiveness, acid and base-responsiveness and cation and amino acid-responsiveness. Meanwhile, this supramolecular π-gel also shows selective fluorescence sensing for Fe 3+ via cation–π interactions with high selectivity and sensitivity, and the detection limit ofMP5-G for Fe 3+ is 6.06 × 10 −8 M. Even more meaningfully, MP5-G could remove Fe 3+ from water solution with excellent recyclability and ingestion capacity, and the Fe 3+ removal rate can reach up to 99.8%. Furthermore, the Fe 3+ coordinated supramolecular gel, MP5-FeG, shows selective fluorescence "turn-on" sensing forl -Cys. The detection limit ofMP5-FeG forl -Cys is 1.0 × 10 −8 M. Simultaneously, thin films based on these supramolecular gels were prepared, which were confirmed to be convenient test kits for detecting Fe 3+ andl -Cys. In addition, these supramolecular π-gels could be used as sensitive ion sensors, sensitive logic gates and fluorescent display materials.